Combined Treatment of Salinity Stress and Fruit Thinning Effect on Tomato - Zhang, Pengfei; Jiang, Shuqin; Dai, Yanyan; Zhang, Zhaorui; Senge, Masateru (Frontiers in Nutrition, 2022)
This was an experimental investigation of the combined treatments of salinity (SAL) stress and fruit thinning (FT) on the growth, yield, fruit quality, and water use efficiency (WUE) of tomatoes with non-soil cultivation. The experiment was carried out in a plastic tunnel, Japan. Tomato (Solanum lycopersicum cv Momotaro) seedlings were transplanted in a randomized complete block (RCB) manner with six plants/ treatment, and an overall 36 plants in 18 pots (2 plants/pot). The experiment involved varying SAL treatment (no-SAL, moderate SAL, and serious SAL, with electroconductivity of 0.8, 3.0, and 4.5 dS m−1, separately) and FT treatment (NT: no thinning and 3FT: three-fruit treatment). The tomato growth, yield, and WUE were significantly suppressed with increasing SAL. In comparison, FT treatment had little effect on tomato growth and water consumption. Either SAL stress or FT treatment significantly improved fruit quality. The combined treatment proved better than single treatment of either SAL stress or FT, and avoided the subsize fruit following SAL stress treatment, reduced fruit cracking found with FT treatment, and greatly improved fruit quality. The SAL thresholds of water use efficiencies in relation to biomass, yield, and marketable yield were approximately 3.0 dS m−1 under these soilless conditions. Path analysis showed that biomass and water consumption were important indexes affecting yield. Logistic equation fitting showed that SAL stress tended to inhibit and delay plant growth; however, FT tended to advance and shorten the period of plant growth.